2007
DOI: 10.1016/s0377-1237(07)80142-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of Clinicobiochemical Spectrum of Hypothyroidism

Abstract: We conclude that hypothyroidism is common and often under-diagnosed. Therefore routine evaluation of female patients with weight gain, generalized weakness, infertility, depression and mood changes should include thyroid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…In this study, they found that the mean age of females with subclinical hypothyroidism is 5.4 years less than hose with overt hypothyroidism. 7 In present study, we found an association in the occurrence of menorrhagia (61.6%) in hypothyroid women. In a retrospective analysis by Andrew D Weeks among 50 patients with myxoedema, 28 (56%) had menstrual disturbances and the most common complaint was menorrhagia (36%).…”
Section: Discussionsupporting
confidence: 56%
“…In this study, they found that the mean age of females with subclinical hypothyroidism is 5.4 years less than hose with overt hypothyroidism. 7 In present study, we found an association in the occurrence of menorrhagia (61.6%) in hypothyroid women. In a retrospective analysis by Andrew D Weeks among 50 patients with myxoedema, 28 (56%) had menstrual disturbances and the most common complaint was menorrhagia (36%).…”
Section: Discussionsupporting
confidence: 56%
“…In this study, they found that the mean age of females with subclinical hypothyroidism was 5.4 years less than those with overt hypothyroidism. 10 37.5% of cases of hypothyroid (both subclinical and overt) in our study, were exhibiting menorrhagia. The similar results were seen in 57.13% patients in the study by Nair RV et al and in 46.15% patients in the study by Bharucha M et al 11,12 Douglas et al observed that 22.3% of cases with menorrhagia had subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 48%
“…[23] Several other studies also have reported a high prevalence of subclinical hypothyroidism among Indians. [24] Among patients from coastal Andhra Pradesh, Shekhar et al 2011 had observed a prevalence of 8.29% for subclinical hypothyroidism [13] and our prevelance was 7.86. Similar to most studies a higher number of women subjects were detected with subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 57%